An analysis of contingency statements in a DRO procedure: A case report. (18th July 2013) - Gerow, Stephanie; Rispoli, Mandy; Boles, Margot B.; Neely, Leslie C.
Abstract: Objective : To examine latency to criterion for reduction of challenging behaviour with and without stating a contingency statement immediately prior to a DRO procedure. Method : An ABAC design in which A was baseline, B was used to evaluate the efficacy of a DRO procedure, and C was used to evaluate the efficacy of a DRO procedure with a contingency statement. Results : The DRO with the contingency statement intervention was associated with a shorter latency to behaviour change than the DRO procedure without the contingency statement. Discussion : These preliminary findings from this case study highlight the importance of examining the efficiency of behaviour change procedures. Directions for future research are provided.